2015
DOI: 10.1177/1352458515600249
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cerebral vasoconstriction syndrome associated with fingolimod treatment in relapsing–remitting multiple sclerosis three months after childbirth

Abstract: Reversible cerebral vasoconstriction syndrome (RCVS) is characterized by acute thunderclap headache, evidence of vasoconstriction in conventional angiography or magnetic resonance angiography and reversibility of these phenomena within 12 weeks. Some triggering factors, for example drugs such as selective serotonin reuptake inhibitors, sumatriptan, tacrolimus, cyclophosphamide and cocaine, or states such as pregnancy, puerperium or migraine have been described. We describe the case of a 29-year-old woman with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…10/mm 3 (10/ mm 3 -29/mm 3 ). Oligoclonal bands were positive in two patients; one of these had a comorbid multiple sclerosis [4]. Cytological analysis revealed a lymphomonocytic pleocytosis in four cases and granulocytes and lymphocytes in one patient.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…10/mm 3 (10/ mm 3 -29/mm 3 ). Oligoclonal bands were positive in two patients; one of these had a comorbid multiple sclerosis [4]. Cytological analysis revealed a lymphomonocytic pleocytosis in four cases and granulocytes and lymphocytes in one patient.…”
Section: Resultsmentioning
confidence: 91%
“…Seven of 10 patients were considered to be exposed to RCVS, provoking triggers such as postpartal status (two patients) and vasoactive medication or drugs such as fluoxetine, tiotropium bromide or consumption of cannabis. In one patient RCVS occurred in the context of medication with fingolimod, which has been incriminated as a provoking factor elsewhere [4]. Strokes were detected in nine of 10 patients; one patient showed cortical subarachnoid haemorrhage in two locations.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A variety of rare AEs associated with fingolimod treatment have been reported as single case reports or small case series including but not limited to posterior reversible encephalopathy syndrome, 68 cryptococcal meningoencephalitis and disseminated cryptococcosis, 69 , 70 Kaposi sarcoma, 71 tumefactive demyelination, 72 74 severe autoimmune hemolytic anemia, 75 asthma deterioration, 76 amenorrhea, 77 peripheral vascular adverse effects, 78 ecchymotic angioedema-like cutaneous lesions, 79 reversible cerebral vasoconstriction syndrome, 80 lymphomatoid papulosis, 81 and hemophagocytic syndrome (this rare disorder due to cytokine dysregulation has been reported in association to infection in two patients treated with fingolimod for 9 and 15 months, respectively, both with fatal outcome). 82 , 83…”
Section: Fingolimod Safety and Tolerabilitymentioning
confidence: 99%
“…To diagnose newly-onset IDD during puerperium, a combination of acute neurological function impairment, typical neuroimaging changes, evidence of positive serum antibodies is needed. Furthermore, it is essential to rule out reversible posterior leukoencephalopahy syndrome[67] and other intracranial multifocal diseases. Although previous reports confirmed that epidural anesthesia and cesarean delivery were innocuous, cesarean section was the main delivery way in this study.…”
Section: Discussionmentioning
confidence: 99%